A review on thermophotovoltaic cell and its applications in energy conversion: Issues and recommendations - Gamel M.M.A.; Lee H.J.; Rashid W.E.S.W.A.; Ker P.J.; Yau L.K.; Hannan M.A.; Jamaludin M.D.Z. (MDPI, 2023)
Cells; Conversion efficiency; Cytology; Gallium arsenide; Global warming; III-V semiconductors; Narrow band gap semiconductors; Semiconducting gallium arsenide; Semiconducting indium; Semiconducting indium gallium arsenide; Semiconductor alloys; Structural design; Waste heat; Anthropogenic activity; Cell conversion efficiency; Gallium antimonide; Generation of electrical energy; Indium gallium arsenide; Issues and challenges; Thermophoto voltaic cells; Thermophotovoltaic systems; Semiconducting antimony compounds